TEACHING TRANSLATION BY USING A COOPERATIVE WORK PROCEDURE - Hartono, Rudi (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2011)
Translating Indonesian texts into English versions is a complicated task for students to do. It isshown by them when they do translation in the classroom. The problems usually come intotheir mind when they have to search equivalent words, appropriate grammar and acceptedstructure for target language they will produce. This scene can be observed when they dotranslating activity individually. They just do it themselves without doing collaboration with theirfriends. They only look up a dictionary and think of it themselves. In this situation a teacher justassigns the task and assesses it, no more to do. As a result, the translation products of thestudents are poor. Therefore, in order to improve the studentsÃ¢â¬â¢ translation ability and quality oftranslation, the teacher should teach the students translation by using a Cooperative WorkProcedure (CWP) in their translation process. This procedure can lead the students be able totranslate well and produce good translation products because they do translating process in acollaborative group.